Edukasi Pemanfaatan Aplikasi Ayat untuk Meningkatkan kualitas Hapalan Quran Santri RQ Azmuna Desa Pematang Berangan kabupaten Rokan Hulu - rahman, syahrul; Azimah, Nur (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2025)
This service activity aims to educate and motivate the santris of RQ Azmuna always to maximize all the potential available to memorize the Quran. This Quran House, located in Pematang Berangan Village, Rokan Hulu Regency, is important in grounding the Quran for the local community. Especially students who study in the capital city of the Regency are able to take RQ Azmuna as a place to live as well as a place to memorize the Quran. In today's digital era, utilizing the digital Qur'an is an alternative tip that can be used to memorize the Qur'an. The technique used in this service is the gradual delivery of material, training, as well as practice from the students of the Quran House. Living in an environment that has been conditioned by the life of the Quran, it becomes an easy trigger for someone to interact more intensely with the Quran. In the Rumah Quran, the students can synergize and help each other to strengthen memorization. This article describes how the students step if they want to repeat memorization while they are not near a muhafizh teacher or friend. The presence of a muhafizh teacher is very meaningful for memorizers, the absence of a muhafizh teacher sometimes reduces their enthusiasm in memorizing the Qur'an. This article presents an alternative solution for memorizers who do not have a muhafizh teacher. The Ayat application can be used as a medium for memorizers. The use of applications is considered effective for memorizers at the college level.